IMPLEMENTASI EKSTRAKURIKULER PENCAK SILAT DALAM PENGUATAN PENDIDIKAN KARAKTER DISIPLIN DI SEKOLAH DASAR PERSATUAN ISLAM SERANG - Toip, Muhamad; Hakim, Zerri Rahman; Hendracipta, Nana (JURNAL PENDIDIKAN DASAR PERKHASA: Jurnal Penelitian Pendidikan Dasar, 2026)
This study aimed to describe the implementation of pencak silat extracurricular activities in strengthening students’ discipline character at Persatuan Islam Elementary School, Serang. The study was motivated by the importance of developing discipline from an early age through contextual and engaging activities. Pencak silat, as a traditional Indonesian martial art, embodies values of discipline, responsibility, and respect aligned with character education goals. The research employed a descriptive qualitative method, with data collected through observations, interviews, and documentation involving the principal, teachers, coaches, and students. Data analysis followed the Miles and Huberman model. The findings showed that pencak silat activities were implemented through structured planning, execution, and evaluation. Discipline values were instilled through habits such as punctual attendance, adherence to rules, and respect for coaches and peers. Challenges, including limited facilities and students’ varying levels of understanding, were addressed through role modeling and educational approaches. In conclusion, pencak silat extracurricular activities significantly contribute to the development of students’ discipline character while also serving as a means of preserving local cultural heritage in elementary schools.